EXTRACELLULAR PHYTASE PRODUCTION BY BACILLUS SP. T4 USING SOLID STATE FERMENTATION - J. Lee; I. Park1and J. Cho (Journal of Animal and Plant Sciences, 2014)
Wheat bran, soybean meal, corn flour and the combinations of these individual substrates with nutritive supplements containing 1% casein hydrolysate, 0.2% CaCl22H2O, 0.4% (NH4)2SO4, 0.02% MgSO47H2O, 0.05% KH2PO4 and0.04% K2HPO4 were evaluated to select an optimal medium in solid state fermentation (SSF) to produce extracellular phytase from a bacterial strain, Bacillus sp. T4. The combination of corn flour with nutritive supplements resulted in best phytase synthesis and was used for further SSF explorations. Maximum phytase production (20787±39 U/g) was observed at a growth period of 84 h, 55.5% moisture content, and 4% inoculum density. Optimum pH for phytase production was 7.0. Enzyme activity was enhanced (P<0.05, 16496±187 to 18304±187 U/g) in the presence of glucose and galactose as a carbon source. The additional nitrogen sources impaired (P<0.05) the phytase activity, and corn steep liquor and sodium nitrateseverely inhibited the enzyme synthesis. T4 phytase produced in SSF may be a promising strategy for upgrading the nutritional quality and combating environment pollution in the feed industry.
Keywords: Solid state fermentation; phytase; Bacillus sp.; feed industry